E-Commerce Analysis In Shariah Business Perspective Through Tokopedia Users - Tubagus Maulana Akbar (IECON: International Economics and Business Conference, 2024)
The development of e-commerce has changed the paradigm of classical business by creating a new model of interaction between producers and consumers in cyberspace. The payment system in trade that previously relied on physical meetings between sellers and buyers has now transformed into a tele-marketing concept, which allows long-distance transactions via the internet without requiring direct face-to-face meetings. This study aims to analyze the concept of e-commerce in Islamic business, especially in the application of sharia contracts on e-commerce platforms such as Tokopedia. Using a descriptive qualitative approach with informants from students and housewives who shop at Tokopedia, this study found that Tokopedia has not fully met the principles of buying and selling in Islam. This is due to the existence of elements that have the potential to contain usury, such as online loans, installment systems, and cashback promos, which some scholars consider to be in the category of usury. However, on the other hand, Tokopedia has begun efforts to implement sharia principles by introducing payment methods through Islamic banks, cash on delivery (COD) transactions, and the “Tokopedia Salam” service which is oriented towards Islamic nuances. The findings of this study indicate that although Tokopedia is not yet completely free from usury, there are efforts to adjust to sharia principles that provide alternatives for Muslim consumers. This study is expected to be a reference for the development of e-commerce businesses that are more in accordance with Islamic principles